The Construction and Interpretation of Combined Cross-Section and Time-Series Inequality Datasets - Joseph F. Francois; Hugo Rojas-Romagosa (Tinbergen Institute, 2005)
The inequality dataset compiled in the 1990s by the World Bank and extendedby the UN has been both widely used and strongly criticized. The criticisms raisequestions about conclusions drawn from secondary inequality datasets in general. Wedevelop techniques to deal with national and international comparability problemsintrinsic to such datasets. The result is a new dataset of consistent inequality series,allowing us to explore problems of measurement error. In addition, the new data allowus to perform parametric non-1inear estimation of Lorenz curves from grouped data.This in turn al1ows us to estimate the entire income distribution; computing alternativeinequality indexes and poverty estimates. Finally, we have used our broad1y comparabledataset to examine international patterns of inequality and poverty.
Keywords: D31; C80; O15; 330; Income distribution datasets; inequality trends; Lorenz curve estimation; poverty estimation; Einkommensverteilung; Einkommensstatistik; Lorenz-Kurve; Gini-Koeffizient; Statistische Methode; Zeitreihenanalyse; Theorie